Influence of aluminium-alloy remelting on the structure and mechanical properties - Cagala, Michal (Materiali in tehnologije, 2013)
The aim of this work was to assess the repeated-remelting influence upon the mechanical properties, thermomechanical properties, chemical composition and structure changes of the selected material. An Al-Cu-type aluminum alloy was chosen on the basis of the ever increasing experiments with non-ferrous metals in the industry. The technical nomenclature of the selected alloy is RR.350 according to the German standard ALUFOND 60. The RR.350 alloy is known for its poor foundry properties which deteriorate due to remelting and affect mechanical properties and the cast-material structure. This negative influence upon the structure and usable properties of a re-melted alloy is further confirmed in the submitted paper. The samples for tensile-strength determination were cast into a metal mould. The gating system and the riser, which served as a charge for the second melt, were removed from the casting. In this way we re-melted the material four times. The samples were machined and ruptured within the temperature range between 20 °C and 350 °C. A sample for metallography and hardness determination (HBS) was taken from the cast material. It can be seen in the tensile-strength diagram that the mechanical properties of the first melt are higher, by 11 % at the temperature of 20 °C, than the properties of the third melt. This difference is evident up to 100 °C. At the temperatures of above 100 °C the cast-material strength characteristics are the same. This tendency shows itself on all the materials tested so far. The hardness and microhardness evaluations show that the material reaches the highest values with the fourth melt. This phenomenon is attributed to the repeated reoxidation and exclusion of oxide membranes. Further, the material structure properties and chemical-composition change were evaluated. The results of this study confirmed a negative influence of alloy remelting upon the material properties and structure.
Keywords: aluminijeve zlitine; aluminium alloy; aluminium alloys; metallographic analysis; metalografska analiza; microstructures; mikrostruktura; pretaljevanje; thermomechanical properties; remelting; termične lastnosti; mechanical properties; mehanske lastnosti